KAJIAN TEMPERATUR BETON SAAT PROSES PENGERASAN MENGGUNAKAN FLY ASH SEBAGAI BAHAN TAMBAH SEMEN - Ali Zakariya; Giri Yudhono; Sasri Rosyadi (Jurnal Jalan-Jembatan, 2021)
Bridges usually have massive concrete structures. The massive concrete will cause temperature on the concrete to be overheated when concrete hardening. The impact from this excess heat results in imperfect hydration and thermal crack which can affect the compressive strength of concrete. Simpang Susun Airmadidi Toll Access Bridge has a pile cap and pier structure with a width > 2 meters so that it can be categorized as mass concrete. To reduce heat arising from concrete hydration, additional materials are needed. The supplementary cementitious material that can be used in concrete mixed according to General Specifications of Road and Bridge Construction Works are materials in the form by minerals or waste materials such as fly ash, pozzolan and silica fume. Simpang Susun Airmadidi Toll Access Bridge project is used fly ash. The study was conducted by reading the temperature rise in two specimens with different concrete mixed. Test object 1 using 380 kg pure OPC cement and Test object 2 using 310 kg OPC cement and 100 kg fly ash F class per m3 of concrete. From the evaluation results it can be concluded that replacement of 24,4% cement using fly ash reducing maximum temperature of concrete from 84.4°C to 71.3°C or decreasing about 13.1°C. Thus fly ash can be an alternative environmentally friendly construction material.